Aluminum Combustion under Different Condition: A Review - Haidzar Nurdiansyah; M. Miftahul A; Fabrobi Ridha (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2020)
This paper reviews the collection of literature on aluminum combustion, with an emphasis on various parameters used. These parameters which affect combustion of aluminum are particles size and oxygen content. Aluminum is a material that is often used in combustion processes due to its effortless reactive material and explosive. A large amount of research has been published about combustion in aluminum materials where aluminum can be used as a way to increase propulsion in combustion. The purpose of this paper is to review some aspects that affect combustion in aluminum. It goes on to discuss the particles size differences and the different oxygen content mixture with gas in used. The results of various existing studies show that there is a difference in ignition temperature and burning time effect in aluminum combustion due to the size and oxygen content. Where, decreasing particles size can decrease ignition temperature and burning time. The review paper is intended to outline a parameter range for aluminum combustion.